1991
DOI: 10.1002/jhrc.1240140711
|View full text |Cite
|
Sign up to set email alerts
|

A trapping column for the coupling of reversed‐phase liquid chromatography and capillary gas chromatography

Abstract: SummaryA new technique for coupling reversed-phase liquid chromatography (RPLC) with gas chromatography is described. A fraction eluting from an RPLC column is trapped on a short column packed with polymeric adsorbent. After the mobile phase has been displaced with water, the analytes are desorbed with ethyl acetate. Following a delay time to enable the water to be flushed to waste, the ethyl acetate containing the analytes is introduced into the gas chromatograph under conditions suitable for partially concur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The first application of on-line LC-GC for PAH determination in vegetable oils dates back to 1991 [ 102 ]. The authors used a silica column to isolate the PAH fraction, which was then transferred to the GC-MS. Moret et al [ 103 ] developed a method to analyze PAHs in oil and lipid extract using a normal phase (NP) silica column coupled on-line with a reversed-phase (RP)-HPLC (C18 column) and an FLD detector.…”
Section: Pah Determination In Vegetable Oilsmentioning
confidence: 99%
“…The first application of on-line LC-GC for PAH determination in vegetable oils dates back to 1991 [ 102 ]. The authors used a silica column to isolate the PAH fraction, which was then transferred to the GC-MS. Moret et al [ 103 ] developed a method to analyze PAHs in oil and lipid extract using a normal phase (NP) silica column coupled on-line with a reversed-phase (RP)-HPLC (C18 column) and an FLD detector.…”
Section: Pah Determination In Vegetable Oilsmentioning
confidence: 99%
“…Vreuls et al used a short trapping column packed with a polymeric sorbent (as used in SPE-OC), to interface RPLC and PC [161]. PAHs were separated by LC using methanol-water as eluent.…”
Section: Figure 18mentioning
confidence: 99%
“…Several authors have reported different approaches for on-line RPLC-GC analysis including direct introduction of the eluent from a micro-LC system into the GC (Cortes et al, 1989;Duquet et al, 1988), the use of retention gaps (Goosens et al, 1991(Goosens et al, , 1994Grob and Artho, 1991), employment of phase switching from the aqueous phase to an organic solvent (Mol et al, 1993;Staniewski et al, 1992;Vreuls et al, 1991a), or intermediate trapping of analytes in a solid phase followed by thermal desorption (SPE-TD) (Vreuls et al, 1991b(Vreuls et al, , 1993. However, various aspects mainly related to (a) the increase of the volume transferred from LC into GC and (b) the speed of sample evaporation have avoided the development of the technique.…”
Section: Introductionmentioning
confidence: 99%